Identification of Poor-outcome Biliopancreatic Carcinoma Patients With Two-marker Signature Based on ATF6α and p-p38 "STARD Compliant". Issue 45 (November 2015) - Martinez-Useros, J.; Georgiev-Hristov, T.; Borrero-Palacios, A.; Fernandez-Aceñero, M.J.; Rodríguez-Remírez, M.; del Puerto-Nevado, L.; Cebrian, A.; Gomez del Pulgar, M.T.; Cazorla, A.; Vega-Bravo, R.; Perez, N.; Celdran, A.; et al.
Abstract : Abstract: Biliopancreatic cancer is one of the most aggressive solid neoplasms, and incidence is rising worldwide. It is known that ATF6α is one of the transmembrane proteins that acts crucially in endoplasmic reticulum stress response, and knockdown induces apoptosis of pancreatic cells. Apart from this, p-p38 has been previously correlated with better outcome in pancreatic cancer. Interestingly, ATF6α knockdown pancreatic cells showed increased p-p38. The aim of this study was to evaluate the expression of these 2 proteins, p-p38 and ATF6α, and their correlation with the outcome of biliopancreatic adenocarcinoma patients. Samples from patients with biliopancreatic adenocarcinoma that underwent pancreaticoduodenectomy from 2007 to 2013 were used to construct a tissue microarray to evaluate p-p38 and ATF6α proteins by immunohistochemistry. We observed that both markers showed a tendency to impact in the time to recurrence; then a combination of these 2 proteins was analyzed. Combination of ATF6α high and p-p38 low was strongly associated with a higher risk of recurrence (hazard ratio 2.918, P  = 0.013). This 2-protein model remained significant after multivariate adjustment. We proposed a 2-protein signature based on ATF6α high and p-p38 low as a potential biomarker of risk of recurrence in resected biliopancreatic adenocarcinoma patients.